The colour of wine: Tasting change - Perlman, Harriet; Sharon Cort; Jaci de Villiers (Botha Hill, KwaZulu Natal : Kalipha foundation, 2018)
he Colour of Wine isn't just another book about picturesque Cape vineyards. Instead, it tells the remarkable story of South Africa's transition from apartheid to democracy through the personal journeys of black winemakers. Woven through their stories are interviews with wine producers and politicians, chefs and sommeliers, connoisseurs and teachers, drinkers and tasters. The book, twinned with the documentary film The Colour of Wine (included on DVD), explores the turbulent history of winemaking in South Africa, and the varied careers the industry has to offer. Wine doyen John Platter offers insights into where South African wine is now, and where the industry needs to go. You'll also discover a rich array of local recipes that complement South African wines. The Colour of Wine gives a taste of the changing world of South African wine.
Making wine. From herding cattle to making wine / Dumisane Mathonsi -- Nothing on a silver plate / Carmen Stevens -- Becoming visible / Unathi Mantshongo -- Like climbing Table Mountain / Ntsiki Biyela -- From vineyard to cellar -- For the love of wine. The world of wine. A short history of wine in South Africa / Michelle Hay -- Education and career opportunities / Wesley Thompson -- Tasting wine. The business of wine. A Soweto wine merchant / Mnikelo Mangciphu -- An unexpected career / Nkululeko Mkhwanazi -- Judging wine / Michael Fridjhon -- From stockbroker to wine producer / Raymond Ndlovu -- The world of parties and entertainment / Tebello Motsoane -- Wine and work. The future of wine. The next glass / John Platter -- The ritual of wine. Food and wine. An African chef / Nompumelelo Mqwebu. South African snapper. amaDumbe gnocchi. umKantsha; isiJingi -- A sommelier's journey / Bongani Nqwenya. Cajun seared salmon. Mussel and prawn chowder. Grilled red roman -- Getting away from the noise / Sithembiso Mthethwa. Rabbit stew -- South African food and wine in New York City / Suzaan Hauptfleisch -- No rules to taste / Florence Fabricant -- Food and wine
Includes acknowledgements
Adult
Keywords: Vintners Wine industry South Africa History; Vintners Wine industry South Africa History -- Wine industry$1 (BSouth Africa$1 (BHistory Black vintners$1 (BSouth Africa Wine industry$1 (BSouth Africa Vintners$1 (BSouth Africa Vintners$1 (BSouth Africa$1 (BHistorys